Insulin Promotes Survival of Amyloid-Beta Oligomers Neuroblastoma Damaged Cells via Caspase 9 Inhibition and Hsp70 Upregulation. (13th May 2010) - Di Carlo, M.; Picone, P.; Carrotta, R.; Giacomazza, D.; San Biagio, P. L.
Abstract : Alzheimer's disease (AD) and type 2 diabetes are connected in a way that is still not completely understood, but insulin resistance has been implicated as a risk factor for developing AD. Here we show an evidence that insulin is capable of reducing cytotoxicity induced by Amyloid-beta peptides (A-beta) in its oligomeric form in a dose-dependent manner. By TUNEL and biochemical assays we demonstrate that the recovery of the cell viability is obtained by inhibition of intrinsic apoptotic program, triggered by A-beta and involving caspase 9 and 3 activation. A protective role of insulin on mitochondrial damage is also shown by using Mito-red vital dye. Furthermore, A-beta activates the stress inducible Hsp70 protein in LAN5 cells and an overexpression is detectable after the addition of insulin, suggesting that this major induction is the necessary condition to activate a cell survival program. Together, these results may provide opportunities for the design of preventive and therapeutic strategies against AD.